The Nether World of Academic Librarians: Issues of Classification, Educative Mission, and Sense of Place - Bernstein, Alan (My University, 2009)
This mixed-methods study examined correlations between academic librarian organizational classification and sense of place (defined as job satisfaction and personal motivation) and sense of involvement with the educative mission of the institution. Further, this study examined whether there were any significant correlations between academic librarian career path and their sense of place and sense of involvement with the educative mission. An abundance of literature on academic librarians" organizational classification maintains librarians ought to be classified as faculty with commensurate rights and privileges. An often tacit implication of this position is academic librarians classified as faculty are (or would be) happier and have a greater sense of involvement with their school's educative mission. The study surveyed 372 academic librarians at colleges and universities in the University System of Georgia. Analysis of surveys found there were no statistically significant correlations between organizational classification and sense of place or between organizational classification and sense of involvement with the institution's educative mission. Analysis of surveys further found that there were no statistically significant correlations between career path and sense of involvement with the institutional educative mission and there was a slight positive correlation between career path and sense of place. It was concluded though there is strong support and justification for academic librarians being classified as faculty, an academic librarian's sense of place or sense of involvement with the institutional educative mission is not dependent on such classification.
Keywords: Academic Librarian Organizational Classification; Sense of Place; Sense of Involvement; Librarians; libraries